Heterologous expression of hyperthermophilic cellulases of archaea Pyrococcus sp. by fungus Talaromyces cellulolyticus - Kishishita, Seiichiro (J Ind Microbiol Biotechnol, 2014)
Talaromyces cellulolyticus (formerly known as Acremonium cellulolyticus) is one of the high cellulolytic enzyme-producing fungi. T. cellulolyticus exhibits the potential ability for high amount production of enzyme proteins. Using the homologous expression system under the control of a glucoamylase promoter, some kinds of cellulases of T. cellulolyticus can be expressed by T. cellulolyticus. On the other hand, hyperthermophilic cellulase has been expected to be useful in the industrial applications to biomass. The hyperthermophilic archaea Pyrococcus horikoshii and P. furiosus have GH family 5 and 12 hyperthermophilic endocellulase, respectively. The two kinds of hyperthermophilic endocellulases were successfully produced by T. cellulolyticus using the above expression system under the control of a glucoamylase promoter of T. cellulolyticus. These recombinant cellulases exhibited the same characteristics as those of the recombinant cellulases prepared in E. coli. The productions of the recombinant enzymes were estimated to be over 100 mg/L. In this study, we first report the overexpression of the hyperthermophilic enzymes of archaea using the fungal expression system.